The Limits of Socio-Legal Radicalism: Social and Legal Studies and Third World Scholarship. (December 2017) - Harrington, John; Manji, Ambreena
In this review to mark the 25th anniversary of Social and Legal Studies ( SLS ), we offer an assessment of the evolution of socio-legal scholarship on the Third World. We seek to locate the journal in the broader history of socio-legal studies and legal education in the United Kingdom and to consider its engagement with the work of Third World scholars. In order to do this, we recall the founding commitment of the journal's first editorial board to non-western perspectives on law and locate this commitment both historically and biographically. We explore a number of important interventions concerned with socio-legal studies in the Third World, but also point to significant gaps and omissions since 1992. To end, we argue for a reassertion of SLS 's founding commitments to anti-imperial scholarship and the challenges posed by critical, non-western perspectives.